Quantitative phylogenomic evidence reveals a spatially structured SARS-CoV-2 diversity - Jones, Leandro Roberto (2020)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is an emergent RNA virus that spread around the planet in about 4 months. The consequences of this rapid dispersion are under investigation. In this work, we analyzed thousands of genomes and protein sequences from Africa, America, Asia, Europe, and Oceania. We provide statistically significant evidence that SARS-CoV-2 phylogeny is spatially structured. Remarkably, the virus phylogeographic patterns were correlated with ancestral amino acidic substitutions, suggesting that such mutations emerged along colonization events. We hypothesize that geographic structuring is the result of founder effects occurring as a consequence of, and local evolution occurring after, long-distance dispersion. Based on previous studies, the possibility that this could significantly affect the virus biology is not remote.